The perception of tourist on the turtle conservation in Malacca. - Hazizi, Haziq Danial; Saad, Mazni (2020)
In the past decade, much research has focused on turtle conservation. It can be seen that the conservation of turtles gives a positive trend in the results. It remains unclear why there are still some turtle conservation places unrenowned by some people. The purpose of this research was to explore the perception of tourists on turtle conservation in Malacca. The data used in this research were collected through face-to-face interviews by using semi- structured interview questions that have been adapted and adopted from the past research. The proposed objectives of this research are to highlight the awareness about turtle conservation among the tourists and to investigate the perception of tourists on the commercialization of the turtle conservation centre. The findings of this research have exposed that the tourists partially agree on the commercialization of the turtle conservation centre and they are conscious of the impact of the turtle conservation commercialization. This research finding helps the local community and tourists in creating the awareness of the turtle conservation centre that underpin the effort of turtle conservation in Malacca.